Prevalence and determinants of xerophthalmia in rural children of Uttarpradesh, India - Agrawal, VK; Agrawal, P; Dharmendra, Dr (Nepalese Journal of Ophthalmology, 2013)
Introduction: Vitamin A deficiency (VAD) is recognized as a major cause of blindness among children in India. Objective: To find out the prevalence of VAD in rural children of Uttar Pradesh, India. Materials and methods: This cross-sectional study was undertaken amongst children (0-15 years) in a rural area of Bareilly (Uttar Pradesh) where the study population was selected by simple random sampling out of villages under a Primary Health Centre. Out of 844 children, 802 participated in the study. The WHO classification of xerophthalmia was used. Results: Overall, the prevalence of xerophthalmia was 5.4 %. The prevalence of Bitot’s spots was 0.9 % in children under six years of age and 3.3 % in children above six years. The prevalence of xerophthalmia was significantly more in older children. Overall, the prevalence of anemia was found to be 11.8 % in the study population. A significantly high prevalence of xerophthalmia (OR= 5.7; 95 % CI = 2.8 - 11.5) was observed in children suffering from anemia. Conclusion: The presence of a milder manifestation of xerophthalmia and a 0.9 % prevalence of Bitot’s spot in children under six years of age in the present study shows a declining trend of VAD although it is still a public health problem. The higher prevalence in children above six years of age shows that apart from strengthening of Vitamin A prophylaxis programs, health education is needed for dietary diversification to include vegetables and fruits in the diet for long-term sustainability in improving the vitamin A status of children of all age groups. Nepal J Ophthalmol 2013; 5(10): 226-229 DOI: http://dx.doi.org/10.3126/nepjoph.v5i2.8733